2013
DOI: 10.1142/s0218301313500900
|View full text |Cite
|
Sign up to set email alerts
|

Critical Scaling of Two-Component Systems From Quantum Fluctuations

Abstract: The thermodynamics of excited nuclear systems allows one to explore the second-order phase transition in a two-component quantum mixture. Temperatures and densities are derived from quantum fluctuations of fermions. The pressures are determined from the grand partition function of Fisher's model. Critical scaling of observables is found for systems which differ in neutron to proton concentrations thus constraining the equation of state of asymmetric nuclear matter. The derived critical exponent β = 0.35 ± 0.01… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
20
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 54 publications
7
20
0
Order By: Relevance
“…These experimental quantities and the corresponding critical values have shown a dependence on the system neutron-proton asymmetry. This paper extends our previous analysis [32][33][34] using protons as probe particles. We now provide additional results from the same experimental data set by Coulomb correcting temperature and density values.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…These experimental quantities and the corresponding critical values have shown a dependence on the system neutron-proton asymmetry. This paper extends our previous analysis [32][33][34] using protons as probe particles. We now provide additional results from the same experimental data set by Coulomb correcting temperature and density values.…”
supporting
confidence: 80%
“…In our recent works [32][33][34], we have reported on the experimental temperatures and densities of fragmenting systems produced in near Fermi-energy heavy-ion collisions by means of a quantum fluctuation method for protons. Since the protons represent the vapor phase, the derived densities and temperatures were shown to sample the vapor branch of the liquid-gas coexistence curve.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The method is described in a very detailed way in [37][38][39][40][41]50]; here we only briefly outline it. The quadrupole momentum is defined as Q xy = p 2 x − p 2 y using the transverse components p x and p y of the particle's momentum in the frame of the QP source.…”
Section: Temperature and Densitymentioning
confidence: 99%
“…Previously [31,32,50] the data were sorted into four different QP asymmetry bins of width 0.05, ranging from 0.04 to 0.24. In a subsequent paper [51], it was shown that values of T and ρ that correspond to an asymmetry bin width close to zero (as it should be for fixed A and Z) could be obtained by averaging values for all four asymmetry bins.…”
Section: Temperature and Densitymentioning
confidence: 99%